(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we establish several new fixed point (FP) theorems for fuzzy mappings in the framework of complete b-fuzzy metric spaces (FMS). We introduce generalized contractive conditions that extend and unify a wide class of existing FP principles in fuzzy and non-fuzzy settings. Our results cover and generalize many classical theorems, and their strength is demonstrated by an application to the existence of fuzzy solutions of nonlinear integral equations. The findings highlight the relevance of b-FMSs in handling uncertainty and imprecision arising in real-world models